Assessing the Feasibility of Complex Recycling of SNF Reprocessing Waste Using RF Torch Air Plasma - Karengin A. G. Aleksandr Grigorievich (Computation, Automation, Information Technologies and Safety Systems in Nuclear Industry, 2015)
Title screen